Immunohistochemical Expression of CD(56) and ALDH(1 )in Common Salivary Gland Tumors - Seifi, Safoura (Iran J Otorhinolaryngol, 2016)
INTRODUCTION: Natural killer (NK) cells, of which CD(56) is a specific marker, play an important role in host defense against tumors. Cancer stem cells, of which aldehyde dehydrogenase isoform 1 (ALDH(1)) is an immunohistochemical marker, are a group of tumorigenic cells which are involved in migration and tumor recurrences. We aimed to evaluate the expression of ALDH(1) and CD(56) in common salivary gland tumors, as well as their relationship with each other and with a number of clinicopathologic factors. MATERIALS AND METHODS: Forty-five paraffin blocks of salivary gland tumors (pleomorphic adenoma, mucoepidermoid carcinoma and adenoid cystic carcinoma, 15 samples each) were selected. Malignant tumors were classified into two groups: low-grade (including mucoepidermoid carcinoma grade I) and high-grade (including mucoepidermoid carcinoma grade III and adenoid cystic carcinoma). Immunohistochemical staining for ALDH(1 )and CD(56) markers was performed. Data were analyzed using SPSS (20) and the Chi-square test. RESULTS: CD(56 )expression was significantly higher in benign and high-grade malignant tumors (P=0.01). ALDH(1) overexpressed in all three salivary tumors, but not to statistically significant degree (P=0.54). There was no statistically significant correlation between ALDH(1) and CD(56) expression with demographic factors (age, gender, or location of tumor; P>0.05). CONCLUSION: It appears that the number of NK cells and their function change in different types of salivary gland tumors (benign/malignant) and stroma. NK cells are important components of the anti-tumor system; therefore immune dysfunction is associated with tumor progression in tumors of the salivary gland. ALDH(1) overexpression suggests its role in tumorogenesis, but ALDH(1) is not involved in the morphogenesis of salivary gland tumors.